HARMONIZING INTERNATIONAL AND NATIONAL LEGAL SYSTEMS THROUGH THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT IN THE MODERN STATE - Siti Sumartini; Tri Setiady (Cepalo)
Sustainable development is a critical concept used to enhance global welfare. In this context, peremptory norms recognized within international law are integrated as general, universal, essential, and fundamental principles for societal benefit. Therefore, this research aimed to investigate the role of sustainable development within international law and examine the contribution of norms to the formation of a modern legal state. The legal status of norms and capacity to embody universal values are clarified using descriptive analysis with a normative juridical approach and qualitative data. The results show that sustainable development has been developed as an indispensable paradigm, widely confirmed across legal frameworks. In addition, the integration as a universal norm within international law reflects the potential to influence legal systems globally. This depends on the balance of established sources such as treaties and customary practices. Moreover, this research contributes to legal scholarship by stating the role of international norms in advancing sustainable development.